Amino Acid Residues 68–71 Contribute to Influenza A Virus PB1-F2 Protein Stability and Functions - Cheng, Yi-Ying; Yang, Shih-Rang; Wang, Ying-Ting; Lin, Yu-Hsin; Chen, Chi-Ju (Frontiers in Microbiology, 2017)
Influenza A virus PB1-F2, encoding a multi-functional protein, is regarded as a virulent gene. Variation in expression pattern and protein stability among PB1-F2 proteins derived from different strains may explain why PB1-F2 functions in a strain- and cell type-specific manner. Because the protein stability of PB1-F2 affects its biological functions, we looked for sequences important for this property. By comparing variants and chimeric of PB1-F2 proteins from A/Hong Kong/156/1997 (H5N1) and A/Puerto Rico/8/1934 (H1N1), we identified amino acid residues 68–71 affect its protein stability. PB1-F2 with T68, Q69, D70, and S71 has a shorter protein half-life than its I68, L69, V70, and F71 counterpart. This is likely to do with proteasome-mediated degradation. Swapping amino acids 68–71 between two proteins reversed not only the length of protein half-life and sensitivity to MG132, but also subcellular localization and interferon antagonization. Our data suggested that composition of amino acids 68–71, which regulates protein stability and therefore its functions, can be a major factor determining strain-specificity of PB1-F2.